2021
DOI: 10.1038/s41698-021-00191-2
|View full text |Cite
|
Sign up to set email alerts
|

A computational method for prioritizing targeted therapies in precision oncology: performance analysis in the SHIVA01 trial

Abstract: Precision oncology is currently based on pairing molecularly targeted agents (MTA) to predefined single driver genes or biomarkers. Each tumor harbors a combination of a large number of potential genetic alterations of multiple driver genes in a complex system that limits the potential of this approach. We have developed an artificial intelligence (AI)-assisted computational method, the digital drug-assignment (DDA) system, to prioritize potential MTAs for each cancer patient based on the complex individual mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…AI-based virtual screening supports the identification of candidate compounds with highly specific selectivity for targeted oncogenic driver aberrations and low toxicity. For example, Istvan et al reported an AI-assisted computational method, which is a proprietary technology of Oncompass Medicine Inc., to prioritize potential molecular targeted therapies based on the complex individual molecular profile of the tumor in each patient [ 100 ]. They analyzed the clinical benefits of the digital drug-assignment system using the data from the SHIVA01 precision oncology clinical trial, and showed that the system identified substantial molecular targets with the fitting inhibitors, including in lung cancer patients, such as FMS Related Receptor Tyrosine Kinase 3 mutation with sorafenib and Androgen receptor expression with abiraterone.…”
Section: Future Direction and Challenges Of Using Ai In Nsclc With Druggable Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-based virtual screening supports the identification of candidate compounds with highly specific selectivity for targeted oncogenic driver aberrations and low toxicity. For example, Istvan et al reported an AI-assisted computational method, which is a proprietary technology of Oncompass Medicine Inc., to prioritize potential molecular targeted therapies based on the complex individual molecular profile of the tumor in each patient [ 100 ]. They analyzed the clinical benefits of the digital drug-assignment system using the data from the SHIVA01 precision oncology clinical trial, and showed that the system identified substantial molecular targets with the fitting inhibitors, including in lung cancer patients, such as FMS Related Receptor Tyrosine Kinase 3 mutation with sorafenib and Androgen receptor expression with abiraterone.…”
Section: Future Direction and Challenges Of Using Ai In Nsclc With Druggable Mutationsmentioning
confidence: 99%
“…Therefore, establishing new framework for analyzing huge size of omics data, such as academia–industry collaboration and academia–government technological collaboration, will be important as well as the AI development. With regard to radiology and molecular targeted therapies, some academia–industry collaborations have successfully complemented each other [ 45 , 46 , 100 ], and AI-based screening has been accelerated toward clinical applications. Prospectively, these frameworks, which can lead to further progression of inter-industry activities, and medical AI systems could be a detector of microchanges in patients that can go unnoticed by human eyes, and be a selector of suitable treatments for individual patients to support clinicians, resulting in more early intervention and in improving the quality of life of patients.…”
Section: Prospectsmentioning
confidence: 99%
“…Tumor mutational burden (TMB) was low (2 mutations/megabase). * AEL: Aggregated Evidence Level, a computed driver evidence score according to the digital drug assignment system [24].…”
Section: Case Reportmentioning
confidence: 99%
“…All exonic variants were analyzed by our digital drug assignment (DDA) system (RealTime Oncology Treatment Calculator™ v1.64) [24]. Based on the scientific evidence in relation to the molecular profile, the system ranked the phosphatidylinositol-3-kinase (PI3K) inhibitors, alpelisib and copanlisib, and the mTOR inhibitor everolimus as of the highest relevance (Table 2).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation